2000
DOI: 10.2308/jis.2000.14.2.127
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Intensional Reasoning in Knowledge-Based Accounting Systems

Abstract: A limitation of existing accounting systems is their lack of knowledge sharing and knowledge reuse, which makes the design and implementation of new accounting systems time-consuming and expensive. An important requirement for knowledge sharing and reuse is the existence of a common semantic infrastructure. In this article we use McCarthy's (1982) Resource-Event-Agent (REA) model as a common semantic infrastructure in an accounting context. The objective is to make knowledge-intensive use of REA to share accou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…To a minor extent, we will also focus on the design cycle by presenting an artefact -namely the exemplar -that will serve as our proof of concept and allow for a scenario-based analysis of our approach presented shortly. This paper addresses research rigour by refactoring the Prolog 1 code found in Geerts and McCarthy (2000a) with notions from the REA formalisation developed by Gailly, Laurier and Poels (2008). That formalism is stereotyped in turn with OntoUML stereotypes (Guizzardi, 2014) instead of OWL stereotypes, and notions from the original ResourceEvent-Agent (REA) data model published by McCarthy (1982) and Hruby et al's (2006) book on REA.…”
Section: Research Methodology and Related Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…To a minor extent, we will also focus on the design cycle by presenting an artefact -namely the exemplar -that will serve as our proof of concept and allow for a scenario-based analysis of our approach presented shortly. This paper addresses research rigour by refactoring the Prolog 1 code found in Geerts and McCarthy (2000a) with notions from the REA formalisation developed by Gailly, Laurier and Poels (2008). That formalism is stereotyped in turn with OntoUML stereotypes (Guizzardi, 2014) instead of OWL stereotypes, and notions from the original ResourceEvent-Agent (REA) data model published by McCarthy (1982) and Hruby et al's (2006) book on REA.…”
Section: Research Methodology and Related Researchmentioning
confidence: 99%
“…The exemplar is a set of statements written in Prolog able to transform dependent view Prolog statements into independent view Prolog statements and vice-versa. To emphasise this paper's embedding in the REA literature, the code in Appendix C and E also shows how an opposing and independent perspective could be derived from Geerts' and McCarthy's (2000a) code. These reference older REA artefacts but nonetheless illustrate this paper's embedding of REA's design science tradition; the illustration is accordingly reinforced by an informed argument.…”
Section: Research Methodology and Related Researchmentioning
confidence: 99%
See 3 more Smart Citations